The Relationship Between Parenting Patterns and the Independence of Elementary School Children - Danniel Peavey Ady Wicaksono; Titik Nurwiati (Konsultan Jurnal Ilmiah Indonesia, 2024)
This article aims to examine the relationship between parental parenting and the level of independence of children at the elementary school level. Children's independence is an important aspect in individual development that is influenced by various factors, one of which is the parenting style applied by parents. The parenting styles analyzed in this study include three types, namely authoritarian, democratic, and permissive parenting. This study uses a literature study method by referring to various sources such as journals and other relevant references. Based on the results of the literature study, this study highlights the importance of the role of parents in building children's independence. Therefore, parents are encouraged to implement parenting styles that can support the development of children's independence so that they can grow into independent individuals and be able to face various challenges in the future.